Anti-prostate cancer metabolites from the soil-derived Aspergillus neoniveus - Fayek, Menna; Ebrahim, Hassan Y.; Elsayed, Heba E.; Abdel-Aziz, Mohamed S.; Kariuki, Benson M.; Moharram, Fatma A. (Frontiers in Pharmacology, 2022)
Prostate cancer (PCa) ranks as one of the most commonly diagnosed malignancies worldwide. Toxicity, lack of clinical efficacy, and development of resistance phenotypes are the main challenges in the control of prostate malignancies. Notably, castration-resistance prostate cancer (CRPCa) is a highly aggressive and metastatic phenotype of the disease with a poor prognosis and very limited therapeutic options. Herein, we report the isolation and genotypic identification of a soil-derived fungus Aspergillus neoniveus using the PCR-based internal transcribed spacer (ITS) region amplification approach. HPLC/MS investigation of the metabolic profile of the ethyl acetate extract from the fungal biomass revealed tentative identification of forty-five compounds belonging to various chemical classes including γ-butyrolactones, alkaloids, phenolics, and quinoids. Furthermore, the chromatographic purification of microbial extract enabled the identification of nervonic acid methyl ester (1) for the first time from endophytic fungi, as well as acetyl aszonalenin (2), and butyrolactone II (3) for the first time from A. neoniveus.. The chemical frameworks of the isolated compounds were identified via extensive spectral analysis including 1 and 2D NMR and MS. The X-ray crystal structure and absolute configuration of acetyl aszonalenin (2) were also determined. Additionally, screening of in vitro anticancer activity of the fungal extract revealed its potential antiproliferative and anti-migratory activities against five different prostate cancer cells (PC3, PC-3M, DU-145, CWR-R1ca, and 22Rv1), including different cells with the castration-resistance phenotype. Moreover, the isolated metabolites significantly inhibited the proliferation, migration, and colonization of human prostate cancer cells at low micromolar levels, thus providing credence for future investigation of these metabolites in relevant anti-prostate cancer animal models. Furthermore, computational target prediction tools identified the cannabinoid G-protein coupled receptors type 1 (CB1) as a potential biological target mediating, at least in part, the anticancer effects of acetylaszonalenin (2). Moreover, molecular modeling and docking studies revealed a favorable binding pose at the CB1 receptor orthosteric ligand pocket aided by multiple polar and hydrophobic interactions with critical amino acids. In conclusion, the Aspergillus neoniveus-derived prenylated indole alkaloid acetylaszonalenin has promising anticancer activity and is amenable to further hit-to-lead optimization for the control of prostate malignancies via modulating CB1 receptors